The The Relationship Between Maternal Knowledge About Nutrition In Toddlers With The Prevention Of Stunting In Kabanjahe - HENNY, HENNY FRANSIS KARNOVA BR PURBA; Eka Purnamasari; Rosmani Sinaga; Yasrida Nadeak; Helmiati Peranginangin; Nadya Nabilla, (Mitra Husada Health Internasional Conference (MIHHICo), 2023)
ABSTRACT Stunting is a condition of growth failure caused by malnutrition and other health problems that result from long-term malnutrition. World Health Organization (WHO). It is estimated that 54% of child deaths in the world are caused by poor nutrition. In Indonesia, nutrition causes more than 80% of child deaths. Globally, Indonesia has the third highest prevalence of stunting in children under five after Timor Leste (50.2%) and India (38.4%). Indonesia (24.4%).This type of research is a survey type with a cross sectional design or where the data collection process is carried out at the same time between the independent variables. To determine the relationship between maternal knowledge about nutrition in toddlers with stunting prevention at PMB HelmiatiKabanjahe in 2023.From the results of 41 respondents, the majority of respondents were found to have good knowledge, namely 20 people (48.8%) and the majority of toddlers were prevented from stunting as many as 34 toddlers (82.9%). There is a relationship between maternal knowledge about nutrition in toddlers with the prevention of stunting at PMB Helmiati, with p-value = 0.01.There is a relationship between nutritional knowledge in toddlers and stunting prevention.It is important for mothers of children under five to continuously improve their knowledge on nutrition and good parenting for their children.